2009
DOI: 10.1097/01.aids.0000363784.96321.43
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and effectiveness of integrating provider-initiated testing and counselling within family planning services in Kenya

Abstract: Provider-initiated testing and counselling is feasible and acceptable in family planning services, does not adversely affect the quality of the family planning consultation and increases access to and use of HIV testing in a population who would benefit from knowing their status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 3 publications
3
45
0
Order By: Relevance
“…Our findings are consistent with the evidence base on facility-based FP/HIV African Journal of Reproductive Health June 2017; 21 (2): 79 integration models, which shows that linkages between FP and HTC can facilitate HTC uptake 3,21 , and also indicates improvements in contraceptive use through various combinations of FP and HIV services 3,4 . Although somewhat limited, the available literature does not provide evidence of negative effects from potentially increased staff time with clients as a result of integrating services, and effects on the quality of FP counseling when adding HTC are reported as positive or mixed 3,21 . The challenges we observed with the delivery of integrated messages echo process evaluation data from several studies on facility-based integration of FP into HIV services, which showed that provision of contraceptive counseling, while improved, was not systematic and was in some cases lower than expected 4 .…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are consistent with the evidence base on facility-based FP/HIV African Journal of Reproductive Health June 2017; 21 (2): 79 integration models, which shows that linkages between FP and HTC can facilitate HTC uptake 3,21 , and also indicates improvements in contraceptive use through various combinations of FP and HIV services 3,4 . Although somewhat limited, the available literature does not provide evidence of negative effects from potentially increased staff time with clients as a result of integrating services, and effects on the quality of FP counseling when adding HTC are reported as positive or mixed 3,21 . The challenges we observed with the delivery of integrated messages echo process evaluation data from several studies on facility-based integration of FP into HIV services, which showed that provision of contraceptive counseling, while improved, was not systematic and was in some cases lower than expected 4 .…”
Section: Discussionsupporting
confidence: 88%
“…17,18 Studies of FP/HIV integration demonstrate acceptability to both patients and providers. [19][20][21] Some cohort studies have documented that integrated services can decrease pregnancy rates 22 and increase uptake of hormonal contraceptive methods. 23,24 Most recently, the first cluster-randomized trial (CRT) of integrating FP into routine HIV care services, conducted in western Kenya, demonstrated an increase in more effective contraception use, from 17% at baseline to 37% one year after integration in the intervention arm.…”
mentioning
confidence: 99%
“…demonstrated the effectiveness of at risk communication at recruiting at risk groups to utilize reproductive and preventative health care [38]. Several studies demonstrate the effectiveness of Youth Peer Education services at referring at risk populations to appropriate clinics [23,13]. When coupled with a voucher system for care, use of clinics increases dramatically [9].…”
Section: Discussionmentioning
confidence: 99%